Provider advice, pregnant persons' expectations, and actual gestational weight gain among United States military health care beneficiaries: a secondary analysis of a randomized controlled trial - Erin Solomon; Abby McPhail; Zoran Bursac; Melissa A. Little; G. Wayne Talcott; Rebecca A. Krukowski (BMC, 2024)
Abstract Introduction : Healthy gestational weight gain (GWG) is associated with improved pregnancy and delivery outcomes. Previous literature shows provider advice and expectations regarding GWG significantly associated with GWG outcomes. In this study, we explore the influence of these factors on GWG in a military population in this secondary analysis of data from a randomized controlled trial. Materials and methods Participants (N = 377) came from a completed randomized controlled trial focused on behavioral interventions for healthy GWG and/or postpartum weight loss among TRICARE beneficiaries. At baseline, participants filled out a 5-item questionnaire assessing provider advice and self-expectations for GWG. For the actual GWG primary outcome variable, we calculated the difference between the weight obtained in the first trimester and the weight obtained at 36 weeks of gestation. We used regression models to assess the predictive ability of expectations about GWG on actual GWG. Results Participants with higher baseline BMIs were more likely to expect excessive GWG as defined by the National Academy of Medicine (NAM; Overweight: 46.3%, Obesity: 65.4%). Participants' expectations showed a significant association with actual GWG (OR 2.1, 95% CI 1.29-3.41, p = 0.003). Most participants (64.7%) reported no provider advice about how much weight to gain during their pregnancy. Of those who did receive advice, 55.4% reported that it was within the NAM guidelines. Conclusions The study documented infrequent provider advice about GWG in a large sample of TRICARE beneficiaries (i.e., both active duty and non-active duty individuals) and supported an association between self-expectations and later actual GWG. Future studies might test strategies to increase/improve provider advice regarding GWG and to aid pregnant individuals in shaping and achieving their GWG expectations. Clinical Trial Registration The trial was prospectively registered on clinicaltrials.gov (NCT 03057808) on February 20, 2017.